2020
DOI: 10.1038/s41598-020-71402-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired brain homeostasis and neurogenesis in diet-induced overweight zebrafish: a preventive role from A. borbonica extract

Abstract: overweight and obesity are worldwide health concerns leading to many physiological disorders. Recent data highlighted their deleterious effects on brain homeostasis and plasticity, but the mechanisms underlying such disruptions are still not well understood. in this study, we developed and characterized a fast and reliable diet-induced overweight (DIO) model in zebrafish, for (1) studying the effects of overfeeding on brain homeostasis and for (2) testing different preventive and/or therapeutic strategies. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 82 publications
5
37
0
Order By: Relevance
“…The Artemia saline diet-induced obese (DIO) zebrafish model was first mentioned in 2010 by the Oka research group and, subsequently, it was reproduced by other research groups. The aforementioned model has also been used to test the effects of some dietary supplement effects on body fat accumulation [ 27 , 59 , 60 , 61 , 62 , 63 ]. DIO zebrafish have subsequently been documented and applied as an induction by overfeeding with commercial feed or through a high calorie diet of corn oil or commercial oil enriched feeds for various obesity study purposes [ 27 , 64 , 65 , 66 ].…”
Section: Obesity: Model Of Choicementioning
confidence: 99%
See 1 more Smart Citation
“…The Artemia saline diet-induced obese (DIO) zebrafish model was first mentioned in 2010 by the Oka research group and, subsequently, it was reproduced by other research groups. The aforementioned model has also been used to test the effects of some dietary supplement effects on body fat accumulation [ 27 , 59 , 60 , 61 , 62 , 63 ]. DIO zebrafish have subsequently been documented and applied as an induction by overfeeding with commercial feed or through a high calorie diet of corn oil or commercial oil enriched feeds for various obesity study purposes [ 27 , 64 , 65 , 66 ].…”
Section: Obesity: Model Of Choicementioning
confidence: 99%
“…Hyperplasia is regulated by the differentiation of multipotent mesenchymal stem cells into preadipocytes that, under appropriate stimulation, can differentiate terminally into mature adipocytes. These adipocytes are capable to storing excess energy as cytoplasmic neutral lipid droplets of different sizes which can exceed 100 micrometers [ 61 , 89 ]. In this regard, it has been reported that flavonoids have great potential.…”
Section: Flavonoids Obesity and Metabolic Syndromementioning
confidence: 99%
“…More recent data obtained in vivo also highlight a preventive protective effect of A. borbonica aqueous extract in a zebrafish diet-induced overweight model in displaying cerebral oxidative stress and blood-brain barrier leakage [30], as well as in a mouse stroke model [31]. Registration at the French pharmacopeia supposes that the medicinal plants are devoid of toxic effects in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in contrast to mammals that have only two main cerebral neurogenic niches during adulthood and a limited capacity to repair the brain, adult zebrafish exhibit numerous neurogenic niches across their brain and an important ability for healing 41 , 44 48 . Consequently, more and more studies investigate the impact of metabolic disorders, such as hyperglycemia and obesity, on brain homeostasis and plasticity 29 , 31 , 49 , 50 . However, there are only a few studies concerning HDL receptor expression in zebrafish, in particular in the central nervous system, and no data regarding their potential involvement in brain plasticity and neurogenesis.…”
Section: Introductionmentioning
confidence: 99%